'Such a life…': Elizabeth Gaskell and Charlotte Brontë*. (2nd July 2016) - Stoneman, Patsy
Abstract : This paper documents the course of Charlotte Brontë's friendship with Elizabeth Gaskell and the events leading to Gaskell's undertaking of her remarkable biography, The Life of Charlotte Brontë (1857). It goes on to suggest elements of Charlotte's life, especially those reflected in her youthful writing, which Gaskell did not know or chose not to represent. Finally the paper considers the mutual impact the two women had on one another as writers whose novels closely succeeded one another during the same few years — Jane Eyre (1847), Mary Barton (1848), Shirley (1849), Cranford (1850), Ruth (1853), Villette (1853), North and South (1854–55) — and summarizes the differences between Gaskell's predominantly optimistic outlook on life, in which women combine a caring role with increased independence, and Charlotte's less hopeful perspective focusing on the plight of unmarried women.